Bi‐allelic loss‐of‐function novel variants in LTBP3‐related skeletal dysplasia: Report of first patient from India. Issue 8 (20th May 2020) - Kaur, Ravneet; Siddiqui, Ishrat; Mathur, Vijay; Jana, Manisha; Kabra, Madhulika; Gupta, Neerja
Abstract: Dental anomalies and short stature (DASS) has been recently identified as a distinct entity, associated with bi‐allelic hypomorphic variants in LTBP3 gene. Only 20 individuals from nine families have been previously reported, with a consistent phenotype of short stature, brachyolmia, and amelogenesis imperfecta. We report the first case from India, with novel radiographic and molecular findings in LTBP3 gene, thereby expanding the phenotypic spectrum of DASS.